2019
DOI: 10.1063/1.5078740
|View full text |Cite
|
Sign up to set email alerts
|

Quantized plasmon excitations of electron gas in potential well

Abstract: Using the Schrödinger-Poisson system in this paper the basic quantum features of plasmon excitations in a free noninteracting electron gas with arbitrary degeneracy is investigated. The standing wave solution of the free electron gas is derived from the corresponding linearized pseudoforce system with appropriate boundary conditions. It is shown that the plasmon excitation energies for

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…One of the most effective hydrodynamic formalism for studying the quantum aspects of plasmas is the Schrödinger–Poisson model 63 , 64 , based on the Madelung quantum fluid theory which originally attempted for the single-electron quantum fluid modeling 65 . It has been recently shown that the analytic investigation of linearized Schrödinger–Poisson system for arbitrary degenerate electron gas provides routes to some novel quantum feature of collective plasmon excitations 66 68 . In current study we use the multistream model in order to investigate the band structure plasmon excitations in streaming plasmas and plasmonic lattices.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective hydrodynamic formalism for studying the quantum aspects of plasmas is the Schrödinger–Poisson model 63 , 64 , based on the Madelung quantum fluid theory which originally attempted for the single-electron quantum fluid modeling 65 . It has been recently shown that the analytic investigation of linearized Schrödinger–Poisson system for arbitrary degenerate electron gas provides routes to some novel quantum feature of collective plasmon excitations 66 68 . In current study we use the multistream model in order to investigate the band structure plasmon excitations in streaming plasmas and plasmonic lattices.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective hydrodynamic formalism for studying the quantum aspects of plasmas is the Schrödinger-Poisson model [59,60], based on the Madelung quantum fluid theory which originally attempted for the single-electron quantum fluid modeling [61]. It has been recently shown that the analytic investigation of linearized Schrödinger-Poisson system for arbitrary degenerate electron gas provides routes to some novel quantum feature of collective plasmon excitations [62,63]. In current study we use the multistream model in order to investigate the band structure plasmon excitations in streaming plasmas and plasmonic lattices.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective hydrodynamic formalism for studying the quantum aspects of plasmas is the Schrödinger-Poisson model [59,60], based on the Madelung quantum fluid theory which originally attempted for the single-electron quantum fluid modeling [61]. It has been recently shown that the analytic investigation of linearized Schrödinger-Poisson system for arbitrary degenerate electron gas provides routes to some novel quantum feature of collective plasmon excitations [62,63]. In current study we use this model in order investigate the quantum interference and phase mixing in electron gases with arbitrary degree of degeneracy, based on the collective quasiparticle orbital concept based on pseudoforce formulation.…”
Section: Introductionmentioning
confidence: 99%